2021
DOI: 10.1038/s41598-021-82801-4
|View full text |Cite
|
Sign up to set email alerts
|

Drosophila oocyte proteome composition covaries with female mating status

Abstract: Oocyte composition can directly influence offspring fitness, particularly in oviparous species such as most insects, where it is the primary form of parental investment. Oocyte production is also energetically costly, dependent on female condition and responsive to external cues. Here, we investigated whether mating influences mature oocyte composition in Drosophila melanogaster using a quantitative proteomic approach. Our analyses robustly identified 4,485 oocyte proteins and revealed that stage-14 oocytes fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 70 publications
2
11
0
Order By: Relevance
“…Previous studies in Atlantic cod [ 27 ], yak [ 28 ], chickens [ 29 ], and insects [ 30 ] also reported similar pathways involved in oogenesis. In addition, in Drosophila [ 31 ], mating-induced oocyte maturation with calcium binding and transport proteins increased, as well as calcium signaling pathways that were also significantly enriched in the present study.…”
Section: Discussionsupporting
confidence: 57%
“…Previous studies in Atlantic cod [ 27 ], yak [ 28 ], chickens [ 29 ], and insects [ 30 ] also reported similar pathways involved in oogenesis. In addition, in Drosophila [ 31 ], mating-induced oocyte maturation with calcium binding and transport proteins increased, as well as calcium signaling pathways that were also significantly enriched in the present study.…”
Section: Discussionsupporting
confidence: 57%
“…Therefore, our finding that ascr#10 improves oocyte maintenance supports the idea that this pheromone communicates a higher demand for quality oocytes in anticipation of mating to promote reproductive success ( 19 , 21 ). In other species, female reproductive physiology is substantially altered by mating, at least in part due to components of the seminal fluid ( 41 ) that can alter the germline ( 42 ) as well as organ systems required to sustain the germline ( 43 , 44 ).…”
Section: Discussionmentioning
confidence: 99%
“…The finding of a large number of ribosomal proteins in the DmSP3 was unexpected given sperm are thought to be transcriptionally quiescent. Therefore, we next compared the representation of ribosomal proteins found in the DmSP3 to three other recent proteomic studies in D. melanogaster which used Lumos Fusion Orbitrap mass-spectrometers, representing the female germline and two somatic tissues; embryo (43), unfertilized oocyte (44), and brain (45). All four tissue/cell types identified most cytoplasmic ribosomal proteins, with a slight underrepresentation of large cytoplasmic subunits in the brain (Fig.…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%